Facile fabrication of a poly(ethylene terephthalate) membrane filter with precise arrangement of through-holes. (26th January 2018) - Kihara, Naoto; Odaka, Hidefumi; Kuboyama, Daiki; Onoshima, Daisuke; Ishikawa, Kenji; Baba, Yoshinobu; Hori, Masaru
Abstract: Although membrane filters are indispensable in biochemical analysis fields, most methods for through-hole fabrication are complex and inefficient. We developed a simple method of fabricating poly(ethylene terephthalate) (PET) membrane filters with a precise arrangement of through-holes for the isolation of circulating tumor cells (CTCs) based on their size. By photolithography and dry etching, highly packed 380, 000 through-holes with a diameter of 7 µm were able to cover a whole area with a diameter of 13 mm. Device fabrication for the size-based capture of rare cells in blood such as CTCs is realized in this study.